“Gadis Kecil” Film Animasi 2D Dengan Teknik Digital Drawing Frame By Frame - Lila Dahlia; Andri Nur Patrio (Institut Seni Indonesia Yogyakarta, 2018)
Tells the story of friendship monsters and a little girl who does not look at the race of living things. All living things can be friendly. An initial work as a work was created as a trial in the manufacture of 2D animated series from preproduction to post-production using a tool in the form of a laptop with intermediate specifications.Created with digital 2D non dialogue techniques, although non dialogue is expected the audience can understand what is being conveyed, this is a challenge in making this animated film. For animating, background assets and effects are all done with digital techniques without reducing the art of traditional techniques because in the end the manufacturing process remains fixed by the process of frame by frame which is not much different from traditional techniques. The creation of a 2D animated film